Alcohol Content In Wine Uses GC-FID - Zulham Anshari; Wita Oileri Tikirik; Nini Sahrianti S; Andi Nursanti (Universitas Muhammadiyah Palu, 2024)
In Indonesia the type of drinks are very diverse, one of them is alcoholic beverages. One of the drinks that contains alcohol is alcohol. Wine is an alcoholic beverage (ethanol) known in India, Srilanka and Indonesia since ancient times. Wine is generally made from coconut nira, nira aren or nira thunder, But there's also wine made of rice or glutinous rice with fermentation. This study attempts to know what percentage of alcohol content to the liqueurs march and he knew the drink liquor containing alcohol is in hamlet taruminding organoleptik with this, the a chemical reagent and GC-FID instruments. The method used a total sampling technique where the population is equal to the number of samples of 3 samples. The results of research on testing the alcohol content of arak using gas chromatography (GC-FID) in Bambu Village, Taruminding Hamlet, the results of organoleptic observations from 3 samples have a liquid texture, as well as different colors, smells and tastes, but they are all the same as characteristics of alcohol, the results of observations using reagents showed that 3 samples were positive for containing alcohol and the results of testing using gas chromatography (GC-FID) found that all samples contained alcohol but the levels were below 5%.